Investment, Exchange Rate and Exports Nexus within the South African Automotive Industry - Habanabakize, Thomas; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2023)
The automotive industry is one of the South African industries that contribute to the manufacturing output and exports and plays important to the country’s economic performance. However, the export volume from this industry depends on various economic factors that include foreign direct investment, domestic investment and exchange rate volatility. The current study aims to determine empirically these three variables on the export volume in the South African automotive industry. To achieve this objective, the authors applied the autoregressive distributed lag (ARDL) model, ECM and causality test on quarterly time series data from 2008 to 2021. The study findings reveal that in the long run, domestic investment has a dominant positive effect on exports from the automotive industry. However, while both domestic investment and exchange rate are inversely related to the export in the short run, foreign direct investment is positively significant to increase export levels. The study recommends, based on these findings, the implementation of strategies that enhance growth in domestic investment and cautious management of foreign direct investment as the latter is more effective in the short run. Additionally, the monetary policymakers should, in each policy introduced and implemented, aim for the stability of the domestic currency and its effect on exports, especially in the automotive industry.